Students talk about school: from the adults' world to Neverland - Angelo, Claudia Laus; Lins, Romulo Campos [UNESP] (Editora Univ Federal Parana, Centro Politecnico, 2016)
The discussion we bring in this paper is part of our reading of students' speeches who attended Middle School in 2009 and 2010. Our purpose is to evidence the meanings they produced about school based in notions of meaning, object, legitimateness and communicative space which compose the Model of Semantic Fields and an essay on Peter Pan's story that allowed us to distinguish that when students speak about school the meanings they produce, on how important is school for their future, go in the direction of the Adults' World. But, when they put themselves inside the school, their speeches were about getting together with friends and the break period, approaching more the Neverland's logic.
Keywords: school; students; meaning; object; communicative space